2014
DOI: 10.3844/ajisp.2014.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cross-Reactive Autoantibody Binding to Bovine Serum Albumin in the D-Galactose-Induced Aging Mouse Model

Abstract: The D-galactose (D-gal)-induced animal model, generated by repeated subcutaneous D-gal injections over approximately 6 weeks, has been frequently used for diabetes and aging research. However, little research has investigated the direct correlation between D-gal and autoantibody formation despite several reports on diabetes-and aging-related autoantibodies. The purpose of this study was to determine whether repetitive injection of D-gal can induce autoantibody production in mice. First, we used Bovine Serum Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…In this regard, D-gal-treated mice were probably sensitised by some unknown endogenous protein(s) that share(s) an epitope with BSA. In previous studies, we confirmed that the IgG antibody cross-reacts with BSA [5, 6]. Many studies have shown that mouse anaphylaxis is mediated by IgE, which stimulates histamine and platelet activating factor (PAF), or by IgG, which stimulates PAF [1012].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this regard, D-gal-treated mice were probably sensitised by some unknown endogenous protein(s) that share(s) an epitope with BSA. In previous studies, we confirmed that the IgG antibody cross-reacts with BSA [5, 6]. Many studies have shown that mouse anaphylaxis is mediated by IgE, which stimulates histamine and platelet activating factor (PAF), or by IgG, which stimulates PAF [1012].…”
Section: Discussionsupporting
confidence: 80%
“…We recently reported on the formation of cross-reactive autoantibodies binding to BSA, but not MSA, in mice subcutaneously injected repeatedly with reducing sugars [5]. Additionally, we confirmed that the formation of this autoantibody is dependent on the route of administration (i.e., not oral or intraperitoneal but only subcutaneous) [6].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previously, we identified the formation of cross-reactive autoantibodies binding to bovine serum albumin (BSA) in the D-gal induced mouse model [14]. We considered whether the formation of autoantibody was D-gal specific.…”
Section: Introductionmentioning
confidence: 99%
“…The D-galactose (D-gal) induced animal model, which is established by the consecutive injection of D-gal for ∼6 weeks, has frequently been used to investigate the influence of excessive AGEs on the body [ 10 13 ]. Previously, we identified the formation of cross-reactive autoantibodies binding to bovine serum albumin (BSA) in the D-gal induced mouse model [ 14 ]. We considered whether the formation of autoantibody was D-gal specific.…”
Section: Introductionmentioning
confidence: 99%